(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The Author analyzes, upon first reading, the recent ordinance by the Tribunal of Milan, Sez. I civ., published on April 18th 2017. This ordinance recognizes to a fertile couple the right to access to medically assisted reproduction and to pre-implantation genetic diagnosis, in order to obtain the implantation in the uterus of healthy embryos. The judge orders to the Polyclinic of Milan to provide this service either directly or indirectly, through other healthcare structures. The ordinance follows the Constitutional Court decision n. 96/2015 and is also in agreement with the principle above mentioned.